2021
DOI: 10.1002/mame.202100450
|View full text |Cite
|
Sign up to set email alerts
|

Cetyl Trimethyl Ammonium Bromide Modified Montmorillonite‐Doped Tasar Silk Fibroin/Polyvinyl Alcohol Blend 3D Nanowebs for Tissue Engineering Applications

Abstract: Cetyl trimethyl ammonium bromide (CTAB) modified montmorillonite (MMT) clay (CTAB-MT) doped, tasar silk fibroin-polyvinyl alcohol blend-based 3D nanowebs are generated through electrospinning technique. The morphological analysis reveals the formation of interlinked 3D nanoweb-like architecture and high surface roughness through scanning electron microscopy (SEM) and atomic force microscopy, respectively. The existence of CTAB-MT in nanowebs is confirmed by Fourier transform infrared and complete exfoliation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Whether it is CA/5-Cl8Q or CA, PEG/5-Cl8Q, from a qualitative point of view, their antibacterial activity is not as good as PLA/CTAB/5-Cl8Q. CTAB-MT clay-doped 3D nanowebs [22] showed excellent antimicrobial activity of 97.96% and 90.48% against E. coli and S. aureus bacteria, respectively. Resistance of the PLA/CTAB/5-Cl8Q to E. coli is comparable to the CTAB-MT clay-doped 3D nanowebs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether it is CA/5-Cl8Q or CA, PEG/5-Cl8Q, from a qualitative point of view, their antibacterial activity is not as good as PLA/CTAB/5-Cl8Q. CTAB-MT clay-doped 3D nanowebs [22] showed excellent antimicrobial activity of 97.96% and 90.48% against E. coli and S. aureus bacteria, respectively. Resistance of the PLA/CTAB/5-Cl8Q to E. coli is comparable to the CTAB-MT clay-doped 3D nanowebs.…”
Section: Discussionmentioning
confidence: 99%
“…The CA/5-Cl8Q and the CA, PEG/5-Cl8Q prepared b Spasova et al [29] showed good antimicrobial activities whose measured zones of inhib tion were 4.0 ± 0.18 and 4.5 ± 0.2 cm against S. aureus and around 4.0 ± 0.15 and 4.1 ± 0.2 cm against E. coli, respectively. Whether it is CA/5-Cl8Q or CA, PEG/5-Cl8Q, from a qua itative point of view, their antibacterial activity is not as good as PLA/CTAB/5-Cl8Q CTAB-MT clay-doped 3D nanowebs [22] showed excellent antimicrobial activity 97.96% and 90.48% against E. coli and S. aureus bacteria, respectively. Resistance of th PLA/CTAB/5-Cl8Q to E. coli is comparable to the CTAB-MT clay-doped 3D nanoweb However, the Resistance of the PLA/CTAB/5-Cl8Q to S. aureus is higher than the CTA MT clay-doped 3D nanowebs.…”
Section: Antibacterial Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer, accompanied with lipid and other biocompatible materials, are always updating the drug delivery carriers for a better therapeutic effect, which are mainly promoted by advanced engineering techniques. [1][2][3][4][5][6][7][8] Today, nano techniques are frequently introduced into drug delivery fields for not only renewing the drug delivery systems, [9][10][11][12][13] but also resolving the most difficult pharmaceutical challenges. [14][15][16][17][18] Among them, the dissolution DOI: 10.1002/mame.202300361 of poorly water-soluble drugs and their related controlled release profiles are drawing increasing attention.…”
Section: Introductionmentioning
confidence: 99%